Modeling of Gas Lubricated Compliant Foil Bearings Using Pseudo Spectral Scheme - Balaji Sankar (Japanese Society of Tribologists, 2015)
A methodology for using the pseudo spectral scheme for the modeling of compliant gas lubricated foil bearings is presented in this work. The pseudo spectral scheme is used to obtain numerical solution of the compressible Reynolds’s equation that models the lubricating gas film. This scheme is coupled to a structural model that models the compliant structure of the foil bearing. The coupled simulation model is applied to both one dimensional and two dimensional cases. The simulation model is validated by comparing its results with analytical solution for short bearing case and to published data for compressible two dimensional cases. The advantages of using this scheme compared to a finite volume scheme for the simulation of foil bearings are presented.